Toward Comprehensive Immunization: The Role of Combined COVID-19 and Influenza Vaccines in Public Health - Satish Kumar Sarankar (International Journal of Vaccines, 2024)
The emergence of multi-pathogen vaccines, particularly those combining protection against COVID- 19 and influenza, marks a significant advancement in immunization efforts. These combination vaccines have the potential to streamline vaccination processes, improve vaccine uptake, and reduce the burden on healthcare systems by offering a single dose that targets both viruses. COVID-19 and seasonal influenza are major public health concerns, with overlapping symptoms and seasonal patterns that justify the rationale for a combined vaccine approach. Recent technological advancements, especially mRNA and viral vector platforms, have paved the way for the rapid development of these combination vaccines.This review explores the current progress in developing COVID-19 and flu combo vaccines, highlighting key players, clinical trials, and the potential public health benefits. It also addresses the challenges, such as immune interference, manufacturing complexities, and regulatory hurdles that must be overcome for successful implementation. Furthermore, the implications for public health, including increased vaccination rates, cost- effectiveness, and reduced strain on healthcare systems, are discussed.Ensuring equitable global access and distribution of these vaccines is crucial to their impact, especially in resource-limited settings. Looking forward, the review touches on future innovations, including the development of vaccines targeting other respiratory pathogens and the potential for universal vaccines. The combined COVID-19 and flu vaccine represents a promising step toward more comprehensive and efficient vaccination strategies, contributing to improved global health outcomes.
Keywords: COVID-19; Influenza; Multi-Pathogen Vaccines; Public Health Immunization; mRNA Vaccine Technology